Diseño de una marca turística como estrategia de promoción en el cantón La Maná. - Peñaherrera Toapanta, Betsy Omayra (2024)
The purpose of this research was to design a tourism brand as a promotional strategy for La Maná canton, province of Cotopaxi. For the development of this project, bibliographic research was used, through the review of books, brochures, magazines, and scientific articles related to the design of a tourism brand. Field research helped in the collection of information on tourist attractions for the subsequent updating of the inventory, allowing the identification of the most specific points in La Maná, to consolidate the idea of the brand and finally to identify this canton. As part of the expected results for the construction of the brand, it was established that La Maná has natural and cultural attractions classified in hierarchies I and II. Next, three participatory workshops were implemented with the participation of students, entrepreneurs, and interviews with owners of tourism establishments, whose responses allowed us to generate criteria and more inputs for the development of the tourism brand of this city. Finally, we proceeded to the elaboration of a proposal for a visual identity manual for La Maná, where the isotype, logotype, chromatic, and slogan are specified, with the objective that this brand can be applied adequately, according to the proposal in the development of this research. It is concluded that the brand use manual should be applied to ensure the positioning of the brand that is being designed for this canton, which is suggested to be used by all service providers in the different applications so that the brand of this canton can be positioned.